2005
DOI: 10.1177/194589240501900313
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Effect of Pterygopalatine Fossa Injection with Local Anesthetic and Adrenalin in the Control of Nasal Bleeding during Endoscopic Sinus Surgery

Abstract: Injection of the pterygopalatine fossa resulted in an improved surgical field during endoscopic sinus surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
116
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 17 publications
9
116
1
3
Order By: Relevance
“…Two other studies reflected similar results. 2,9 The current study supports their observation. In another study conducted by Valdes et al, 10 they found no statistical difference between injected and noninjected site in terms of surgical …”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Two other studies reflected similar results. 2,9 The current study supports their observation. In another study conducted by Valdes et al, 10 they found no statistical difference between injected and noninjected site in terms of surgical …”
Section: Discussionsupporting
confidence: 80%
“…There are studies which claim definite decrease in bleeding adopting these techniques as well as those which confront the efficacy of the technique. 2 The current study was done on 32 patients with chronic rhinosinusitis and ethmoidal polyposis. The mean surgical grade on test side was 9.0 ± 3.5 and in control side was 10.9 ± 3.5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 A study published by Wormald PJ et al also supports injecting pterygopalatine canal with xylocaine and adrenaline to see an improved surgical field during endoscopic sinus surgery. 13 Another study was done by Bhardwaj VK, Novonty GM regarding greater palatine canal injection as an alternative to posterior nasal packing and arterial ligation in epistaxis and showed result favoring the procedure. 14 Gurr P et al did a study a study in which Laser Doppler blood flowmetry measurement of nasal mucosa blood flood flow after injection of the greater palatine canal with 2 ml of a 0.5 per cent bupivacaine hydrochloride solution was done.…”
Section: Resultsmentioning
confidence: 99%